1960
DOI: 10.1002/pol.1960.1204213921
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline modifications of cellulose. Part VI. Unit cell and molecular symmetry of cellulose I

Abstract: A study of the electron diffraction diagram of Valonia ventricosa cellulose has confirmed the conclusions reached by Honjo and Watanabe concerning the size of its unit cell. The a and c axes of the cell are twice the length of those usually accepted for cellulose I. The symmetry of the cell is P1, but the evidence available at present does not allow a decision to be made concerning the symmetry of the molecular chains. Consideration of x‐ray diffraction and infrared spectroscopic data suggests that bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…They further suggested that the space-group symmetry of the unit cell was not P21 and implied that twofold screw symmetry was not valid. Fisher & Mann (1960) also working on Valonia ventricosa cellulose, while confirming most of the results of Honjo & Wantanabe (1958), disagreed on the point that individual molecular chains did not possess twofold screw symmetry. Further, Dobb, Fernando & Sikorski (1974) also observed a number of reflections in the electron diffraction patterns of ramie and cotton which could only be indexed in terms of a 'superlattice'.…”
Section: Introductionsupporting
confidence: 57%
“…They further suggested that the space-group symmetry of the unit cell was not P21 and implied that twofold screw symmetry was not valid. Fisher & Mann (1960) also working on Valonia ventricosa cellulose, while confirming most of the results of Honjo & Wantanabe (1958), disagreed on the point that individual molecular chains did not possess twofold screw symmetry. Further, Dobb, Fernando & Sikorski (1974) also observed a number of reflections in the electron diffraction patterns of ramie and cotton which could only be indexed in terms of a 'superlattice'.…”
Section: Introductionsupporting
confidence: 57%
“…[15,16,22 -25,29] The lattice I a is generally present in all algae and bacteria and has a triclinic unit cell structure with one polysaccharide chain. [27,[29][30][31][32] In these two lattices, I a and I b , the conformation of the polysaccharide chains is the same although the hydrogenbonding pattern is different. [33] The I a may be converted into the I b form by annealing the cellulose chains in the solid state.…”
Section: Crystalline Structurementioning
confidence: 87%
“…SHIFT-the stagger of the center chain along its helix axis with re-2) PHI-the coupled rotation of the chains about their respective helix ROT-the rotation of the second chain about its helix axis with re-spect to the glycosidic oxygen of the corner chain at the origin; axes, PHI ,= Oo being arbitrary; spect to the position of the first chain; one molecular parameter:4) x-the dihedral angle which determines the orientation of the -CH2OH group, and has a value of zero when the C(6)-C(6) bond is cis to the C(4)-(5)bond, counterclockwise rotation of the group when looking down the C(5)-C(6) bond representing positive rotation; two orientational parameters: 5) \ko-the center of the Gaussian microfibril distribution in reciprocal 6) CT -the half-width of this distribution; 7) B-the average isotropic temperature factor; 8) K-the scale factor. space, having a value of zero in the a* direction; two crystallographic parameters: (Molecular model of the cellulose chain.…”
mentioning
confidence: 99%